Loneliness in the Older Adult Population - Wilson, Avery C. (East Carolina University, 2022)
Abstract Background: The older adult population is currently facing hardships with increasing rates of loneliness and social isolation. COVID-19 is a large factor in these increasing rates, due to the fact nursing homes, and other elder’s facilities are following strict guidelines for health and safety. By experiencing loneliness, older adult’s health is negatively affected both physically and mentally. Methodology: Through the use of an integrative review, online scholarly articles were found in relation to the topic of interest. Articles focused on the topics of older adult loneliness, technology’s relation to loneliness, and nursing homes. Evaluation and analysis of relevant articles allowed for the relation of technology and reducing effects of loneliness to be evident. Results: Through numerous research and scholarly journals it is proven that technology can reduce the levels of loneliness in people. There are many factors to loneliness, as it effects ones emotional and physical wellbeing. Technology provide the opportunity to allow social interaction even during pandemic isolations. One factor that needs to be further considered is the cost, and complexity of technology for older adults. There ultimately are resources available to diminish this problem, however, it needs to be determined how to most effectively do so. Discussion: This review of literature allows for the gaps between loneliness and older adults to be visible. Further suggestions can be made in order to benefit the population of interest. Additionally, technology can be integrated to older adults to identify if it has the same effects on loneliness as previously found. Keywords: Older adults, integrative review, loneliness, technology
Keywords: Older adults; integrative review; loneliness; technology